Theloderma licin McLeod and Ahmad, 2007 (Lissamphibia: Anura: Rhacophoridae), a New Frog Record for Borneo - Das, I.; Grinang, J.; Yong, M.P (Asian Herpetological Research, 2013)
A new record of the rhacophorid frog, Theloderma licin is reported from Gunung Serambu, in the Bau region of western Sarawak, East Malaysia, which comprises the first published record of the species from the Sundaic island of Borneo. The species was previously known from the Malay Peninsula (southern Peninsular Thailand and Peninsular Malaysia). Species of Theloderma are widespread in mainland and insular Southeast Asia, their arboreal habits perhaps contributing to our perception of rarity.